Detection of genomic imbalances by array based comparative genomic hybridisation in fetuses with multiple malformations - Le Caignec, C (BMJ Group, 2005)
Background: Malformations are a major cause of morbidity and mortality in full term infants and genomic imbalances are a significant component of their aetiology. However, the causes of defects in many patients with multiple congenital malformations remain unexplained despite thorough clinical examination and laboratory investigations. Methods: We used a commercially available array based comparative genomic hybridisation method (array CGH), able to screen all subtelomeric regions, main microdeletion syndromes, and 201 other regions covering the genome, to detect submicroscopic chromosomal imbalances in 49 fetuses with three or more significant anomalies and normal karyotype. Results: Array CGH identified eight genomic rearrangements (16.3%), all confirmed by quantitative multiplex PCR of short fluorescent fragments. Subtelomeric and interstitial deletions, submicroscopic duplications, and a complex genomic imbalance were identified. In four de novo cases (15qtel deletion, 16q23.1–q23.3 deletion, 22q11.2 deletion, and mosaicism for a rearranged chromosome 18), the genomic imbalance identified clearly underlay the pathological phenotype. In one case, the relationship between the genotype and phenotype was unclear, since a subtelomeric 6q deletion was detected in a mother and her two fetuses bearing multiple malformations. In three cases, a subtelomeric 10q duplication, probably a genomic polymorphism, was identified. Conclusions: The detection of 5/49 causative chromosomal imbalances (or 4/49 if the 6qtel deletion is not considered as causative) suggests wide genome screening when standard chromosome analysis is normal and confirms that array CGH will have a major impact on pre and postnatal diagnosis as well as providing information for more accurate genetic counselling.